The Relationship Between Stress Management Techniques with Sleep Quality Disorders in the Elderly - Yohanes Tarigan; Made Dwipa Negara (Jurnal Keperawatan Priority, 2026)
Sleep quality disturbances are one of the problems frequently experienced by the elderly and triggered by stress. This often neglected sleep quality impacts physiological and psychological fulfillment disorders and increases the risk of health problems. The purpose of this study was to find out the relationship between stress management techniques on sleep quality disturbances frequently experienced by the elderly in Nusasari Village. The method used was a pre-experimental study with a one-group pre-test and post-test design. A total of 47 elderly were selected as samples using quota sampling techniques with the criteria of elderly experiencing sleep quality disturbances. The measurement instrument used was the Pittsburgh Sleep Quality Index (PSQI). The research was conducted by providing education on stress management techniques to elderly. Where the right stress management education techniques can help the elderly improve their sleep quality. The tools used by researcher in conducting interventions are PowerPoint and leaflets. Respondents received 30 to 45 minutes of education on the first day and returned on day 3 for a post-test. The results of the study found changes in sleep quality before (PSQI Score Poor=95,7%; Good=4,3%) and after (PSQI Score Poor=6,4%; Good=93,6%) the implementation of stress management technique education. There was a significant improvement in sleep quality (mean 21.50), Z -6.481 and data were analyzed using Wilcoxon Signed Rank Test p < 0.001 (p < 0.005). Providing alternative non-pharmacological interventions by using stress management techniques related to the elderly can improve their sleep quality.